Empat Dimensi Profil Pelajar Pancasila Dalam Perspektif QS. Al-Baqarah Ayat 177 - Afi Rizqiyah; Maulidiyah, Isyfa’; Thobroni, Ahmad Yusam (Risâlah Jurnal Pendidikan dan Studi Islam, 2024)
Quality human resources are those who have noble morals, skills and physical strength whose existence is needed to build the Indonesian state. Factually, the existing human resources are still far from expectations; experiencing moral degradation, low expertise and weak physical strength. The presence of the Pancasila Student Profile is expected to overcome the shortcomings that exist in our education system so far. This research aims to analyze the four dimensions of the Pancasila Student Profile from the perspective of QS. al-Baqarah verse 177 to make it a strong foundation based on religious teachings in order to motivate the community to strengthen the Pancasila Student Profile in shaping quality human resources. This literature research was conducted with a qualitative approach. Data were collected through documentation techniques with primary sources in the form of manuscripts of the Pancasila Student Profile and books that contain interpretations of QS. al-Baqarah verse 177. The data was then subjected to content analysis. The results showed that the four dimensions of the Pancasila Student Profile (the dimension of faith, fear of God Almighty, and noble character; the dimension of mutual cooperation; the dimension of independence; and the dimension of critical reasoning) are documented in QS. al-Baqarah verse 177 and are relevant to the teachings of doing good contained in it, so it can be said that the Pancasila Student Profile reflects the teachings of the Qur'an which should be implemented in shaping quality human resources.